2010
DOI: 10.1111/j.1742-4658.2009.07517.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the substrate specificities of cytochrome c biogenesis Systems I and II

Abstract: c-Type cytochromes require specific post-translational protein systems, which vary in different organisms, for the characteristic covalent attachment of heme to the cytochrome polypeptide. Cytochrome c biogenesis System II, found in chloroplasts and many bacteria, comprises four subunits, two of which (ResB and ResC) are the minimal functional unit. The ycf5 gene from Helicobacter pylori encodes a fusion of ResB and ResC. Heterologous expression of ResBC in Escherichia coli lacking its own biogenesis machinery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…CcdA and CcsX are required for thioreduction of apocyt c thiol groups, whereas CcsAB complex transports heme b to the p side of the membrane, recognizes the apocyt c substrates and forms the thioether bonds between the apocyt c and heme b . Substrate specificity of Ccs is not yet fully established, but it may be as broad as the Ccm-System I [32, 33]. …”
Section: Diversity Of Cytochrome C Biogenesis Systemsmentioning
confidence: 99%
“…CcdA and CcsX are required for thioreduction of apocyt c thiol groups, whereas CcsAB complex transports heme b to the p side of the membrane, recognizes the apocyt c substrates and forms the thioether bonds between the apocyt c and heme b . Substrate specificity of Ccs is not yet fully established, but it may be as broad as the Ccm-System I [32, 33]. …”
Section: Diversity Of Cytochrome C Biogenesis Systemsmentioning
confidence: 99%
“…In prokaryotes, many c-type cytochromes exist in addition to monoheme proteins (17)(18)(19)(20). These are all matured by Systems I and II, consistent with the proposal that only the CXXCH motif is recognized (21)(22)(23)(24). By contrast, the eukaryotic HCCS appears to require a more extended recognition domain than just the CXXCH motif for cytochrome maturation, specifically sequence features or residues located in the cyt c N terminus (see Fig.…”
mentioning
confidence: 48%
“…This also contrasts with the situation in E. coli where CcmG has been shown to be an essential member of the endogenous Ccm system (21). However, and similarly, it has been shown that expression of c-type cytochrome biogenesis System II in a ⌬ccm E. coli strain leads to cytochrome c production without CcmG (or ResA, the analogous protein from System II) (32,44). Normally, CcmG transfers reductant from DsbD to the rest of cytochrome c assembly apparatus and/or the apocytochrome.…”
Section: Discussionmentioning
confidence: 86%